Pengaruh Micro-influencer dan Citra Merek Terhadap Keputusan Pembelian Kosmetik pada Aplikasi TikTok (Studi Kasus Mahasiswa FEB Jurusan Manajemen UNISMA) - Rahma, Putri Anisa; Malikah, Anik; Novianto, Abdullah Syakur (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this study is to analyze the influence of Micro-influencer effectiveness and brand image enhancement on purchasing decisions for cosmetics through the TikTok application, targeting students from the Management Department, Faculty of Economics and Business, Islamic University of Malang. This research employs a quantitative approach with a questionnaire-based data collection technique involving 344 respondents. The independent variables in this study are micro-influencers and brand image, while the dependent variable is purchasing decisions. The findings indicate that micro-influencers have a positive and significant impact on purchasing decisions. Additionally, brand image also has a positive and significant influence on purchasing decisions.This research confirms the important role of micro-influencers in influencing consumer behavior through authentic promotional content on social media. Additionally, a strong brand image increases consumer trust and strengthens purchasing decisions. These results provide implications for developing more effective marketing strategies and improving brand image on social media platforms through the use of micro-influencers. Keywords: Micro-Influencer, Brand Image, Purchasing Decisions, Cosmetics, Tiktok